Inculcating Values in Mathematics Classroom via Problem Solving: Helping Teachers Design Meaningful Lessons - Khalid, Madihah (2018)
Every culture in the world emphasize values which their community members broadly share. These values are inculcated either implicitly or explicitly through family, society and educational institution. Since children spent much of their time at school, it should be a place that supports families’ and communities’ efforts to establish strong values in students. Inculcation of values could be done across the curriculum. However, research on values in mathematics education has only been popular in the past few decades. Since mathematics is imbedded in many different aspects of everyday life, it is an appropriate subject to incorporate values in, which will make students see the relevance of what they are learning better. In this study, teachers were helped in their design of lessons so that meaningful lessons could be produced, in order to ensure effective teaching and learning processes are implemented. This pre-experimental design study involved a combined Year 4 class of 35 students from one international school as research participants. Two teachers participated directly in the study, while some others acted as observers. Both qualitative and quantitative data in the form of observation field notes, interview data (from both students and teachers), tests, questionnaires and observation checklists results were collected. The data was used to answer the research questions on changes in students’ performance and attitude, both in the mathematics topics taught and also on their moral reasoning. The results shows increased but non-significant scores in mathematics. There are also improvements in moral reasoning based on students’ written answers of some moral questions, which is also supported by the interview data. The observation data displays a gradual improvement of students’ in-class behavior in terms of their attitudes towards each other and towards the tasks and activities given. This study implies the possibility for students to learn about morality and values in a mathematics class through careful planning of tasks and activities. It highlights the belief that values can be learned across the curriculum, which is one of the important factors in building a nation of caring and civil society.